Hill placement of manure and fertilizer micro-dosing improves yield and water use efficiency in the Sahelian low input millet-based cropping system - Ibrahim, A.; Abaidoo, Robert C.; Fatondji, D.; Opoku, A. (Elsevier, 2015)
Inadequate nutrient supply and insufficient rainfall are the most important limiting factors for crop production in the Sahelian agro-ecological zones. Targeted technology application may help to improve the efficient use of limited nutrient and water resources. The objective of this study was to determine the optimal combination of fertilizer micro-dosing and manure application rates for improved millet yield and enhanced water use efficiency in low input millet-based cropping system. A two-year field experiment was conducted at a research station in Niger using a randomized complete block design with three replications. The treatments consisted of the factorial combination of: (i) two fertilizer micro-dosing options (20 kg ha−1 of diammonium phosphate (DAP) and 60 kg ha−1 of NPK corresponding to 2 g hill−1 of DAP and 6 g hill−1 of NPK, respectively), (ii) cattle manure at four application rates (0 kg ha−1, 1000 kg ha−1, 2000 kg ha−1, 3000 kg ha−1) and (iii) two methods of manure application (broadcasting and hill placement). Millet grain yields under fertilizer micro-dosing combined with manure was increased on average by 59%, 83% and 113% for 1000 kg ha−1, 2000 kg ha−1 and 3000 kg ha−1, respectively compared with fertilizer micro-dosing alone. Combined applications of manure and fertilizer micro-dosing increased water use efficiency significantly. Hill placement of manure increased total dry matter on average by 23% and water use efficiency by 35% relative to manure broadcasting. The total root length density was increased by 66% and 42% in hill placement of manure at 25 cm and 50 cm, respectively, from the hill centre compared with manure broadcast. These results indicate that millet production with the fertilizer micro-dosing technology can be improved further by hill-placement of manure. The combination of 2000 kg ha−1 of manure and 20 kg DAP ha−1 hill-placed were most promising for increasing millet yield and the efficient use of limited nutrients and water in Sahelian millet based systems. There is need for testing this technology further together with farmers to valuate its effectiveness.